Advanced and innovative simulated moving bed strategy for the isolation of ternary mixtures of triterpenic acids - Azenha, Ivo Samuel Caniceiro (2023)
Biomass residues are increasingly acknowledged to have the potential to replace a large fraction of nonrenewable resources due to their abundance and relative low cost. These residues are a source of natural products with enormous structural and chemical diversity and high added value. Triterpenic acids (TTAs), namely, betulinic, oleanolic and ursolic acids have attracted great research attention due to their wide spectrum of pharmacological and nutraceutical properties. These compounds are ubiquitous in nature and can be found and extracted in relatively high quantities from the outer bark of Eucalyptus globulus, which is a high-volume residue from the pulp and paper industry. Nonetheless, their isolation after extraction is challenging due to their similar molecular structures. The simulated moving bed (SMB) is a continuous chromatographic separation technique that, by operating countercurrently, maximizes the mass transfer driving force, allowing the separation of compounds with low selectivities as, for instance, enantiomers. While a conventional SMB for binary separations is based on a four-zone configuration with synchronous switching of the two inlets and two outlets streams, this technology has been modified continuously through, for example, the addition of inlet and outlet streams, changing the number of zones, and varying concentrations and flow rates to expand its range of application. This thesis includes a detailed review of the most recent SMB strategies. The selection of adsorbents and eluents (or mobile phases) is of primordial importance for the successful operation of an SMB. In this way, a critical literature review covering the solubility of the three TTAs (in unary solvents and mixtures), all types of adsorbents reported for their separation – from commercial adsorbents (C18, C30 and graphite columns) to custom materials (molecularly impressed polymers and others) – eluents (conventional HPLC solvents and super/subcritical fluids), mobile phase modifiers (acidic, basic and cyclodextrins), pre-column derivatization strategies, and the influence of temperature was accomplished. The main results are thoroughly discussed in terms of calculated separation selectivities. The solubilities of TTAs are low in many solvents, increasing with temperature and decreasing sharply with the addition of small quantities of water. Best separation selectivities were obtained with porous graphitic columns. The separation of betulinic, oleanolic and ursolic acids was studied in a first instance at analytical scale with columns Apollo C18, Spherisorb S5, Spherisorb S10 and Acclaim C30 with eluents like methanol, acetonitrile, water, ethanol, isopropanol, ethyl acetate, acetone and mixtures thereof. It was demonstrated that the separation of betulinic and oleanolic acids is fostered with mobile phases containing acetonitrile and methanol (in comparison with pure methanol) for all columns, and that the Acclaim C30 provides the highest selectivities with methanol/acetonitrile 50/50 (%, v/v) emerging as the best mobile phase. In the case of the separation of oleanolic and ursolic acids, the modification of methanol with acetonitrile did not improve selectivity, and the best results were obtained with the column Acclaim C30 and methanol/water 95/5 (%, v/v). The equilibrium and transport parameters for pure TTAs were determined through breakthrough experiments and the method of moments, and were then validated with breakthrough experiments of TTAs binary mixtures. The SMB separations of representative mixtures of natural extracts containing these TTAs were optimized using a design of experiments and surface response methodology combined with phenomenological modeling. The results demonstrated that it is possible to produce betulinic, oleanolic and ursolic acids with purities above 99 % by SMB chromatography. This work culminated with the assembly and start-up of a customized versatile SMB unit. The unit follows a one valve per column configuration (1ST1C) and all its aspects were carefully addressed, from the user interface to the assembly and internal configuration of the valves, and flow rate control. Preparative imChem Surf C30 columns were acquired and carefully characterized in terms of their packing and retention towards the three TTAs. The equilibrium and transport parameters of each TTA were measured by breakthrough experiments with a mobile phase of methanol/water 95/5 (%, v/v; 0.1 % formic acid). The SMB separation of a representative mixture of natural extracts containing betulinic and oleanolic acids was optimized for a minimum purity of 99 %, and various separation experiments were accomplished with four and three zone configurations.